Bibliometric Analysis to Understand Research Trends in Data-Driven Economics - Loso Judijanto; Komang Shanty Muni; Firlie Lanovia Amir (Westscience Press, 2024)
The bibliometric analysis conducted in this study offers a nuanced understanding of the evolution and current state of research within data-driven domains, highlighting